Evaluation of water quality produced by the Mambusao Water District, Mambusao, Capiz - Bayot, Jerilyn Vidal (2002)
The quality of the treated water produced by the Mambusao Water Treatment Plant of Mambusao Water District (MWD), Mambusao Capiz was evaluated.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Drinking water; Water qaulity